The Fluorescent Sensing of BF3 and Amines: A Dual Approach with Hydrazone Ligands - Haichao Ye; Liqin Liu; Dagang Shen; Chang Song; Huanhuan Wang (Sensors)
BF3, volatile amines (VOAs), and biogenic amines (BAs) are the key indicators in chemical reaction catalysis and food quality monitoring. In this study, we present two types of fluorescent sensors, a hydrazone ligand (HL)-based fluorescent sensor for BF3 detection and a novel sensor array using six boron difluoride (BF2) hydrazone complexes (BFHs) for monitoring VOAs and BAs. Spectral research indicates that the interaction mechanism between the HLs and BF3 is based on intramolecular charge transfer (ICT). The HLs for the monitoring of BF3 showed good sensitivity, selectivity, and anti-interference and have the characteristics of a visible color change. Additionally, the HL probe demonstrates reversibility in the presence of triethylamine, making it a candidate for “ON-OFF-ON” mode sensing. BF3 detection can also be efficiently performed using test strips for convenient, air-based applications. The BFH sensor array successfully differentiates histamine from the other typical non-volatile BAs in solution; in comparison, the VOAs are analyzed through recognition patterns and statistical analysis. The array’s color changes enable the practical, on-site detection of shrimp spoilage, with principal component analysis distinguishing various ageing intervals. In summary, this sensor array demonstrates high selectivity for VOAs and BAs, with significant potential for application in real-world sample analysis.